Efektivitas Program Asistensi Sosial Penyandang Disabilitas Berat (ASPDB) di Kota Bandar Lampung - Fitriani, Yuyun (Jurnal Analisis Sosial Politik, 2020)
Abstract The Social Assistance Program for Persons with Severe Disabilities (ASPDB) is a form of state responsibility in fulfilling the rights of persons with disabilities and the embodiment of government social protection for its citizens. The target group of the ASPD program are people with severe disabilities who are unable to carry out activities to fulfill their daily lives so they need help from others. Measurement of effectiveness criteria is based on three main objectives of implementing the ASPDB program, namely: First, the fulfillment of the basic needs of life and daily care for persons with severe disabilities (clothing, food, clean water, daily care) so that their welfare level can be met fairly. Second, the growing concern of families and communities in providing social care and guidance for persons with severe disabilities. Third, growing efforts to fulfill the rights of persons with severe disabilities. Broadly speaking, the effectiveness of the implementation of the ASPDB program in Bandar Lampung has been well implemented. Families of persons with disabilities, which are the main milestones for the growth and development of persons with disabilities, have skills in caring for and looking after persons with disabilities. The community in the neighborhood where persons with disabilities live also do not discriminate against the existence of persons with disabilities so that persons with disabilities can play and interact with the community. Families of persons with disabilities, which are the main milestones for the growth and development of persons with disabilities, have skills in caring for and looking after persons with disabilities. The community in the neighborhood where persons with disabilities live also do not discriminate against the existence of persons with disabilities so that persons with disabilities can play and interact with the community. Families of persons with disabilities, which are the main milestones for the growth and development of persons with disabilities, have skills in caring for and looking after persons with disabilities. The community in the neighborhood where persons with disabilities live also do not discriminate against the existence of persons with disabilities so that persons with disabilities can play and interact with the community.